Effect of Health Education Programme on the Knowledge regarding Hand Washing and Immunization in the Disadvantaged Community of Eastern Nepal (Journal of Nobel Medical College, 2013)
Journal of Nobel Medical College Vol. 2, No.2 Issue 4 May-October 2013 Page 18-23 DOI: http://dx.doi.org/10.3126/jonmc.v2i2.8800